African schools keep an eye on the prize - Jocelyne Sambira (Africa Renewal, 2012)
A small, dusty, sparsely furnished building of mud bricks serves as a classroom for pupils at a primary school in Buterere, a town on the outskirts of Burundi’s capital. The room is packed with a sea of small bodies in khaki uniforms, some sprawling on the dirt floor trying to balance their notebooks and write at the same time. The lucky few who get desks are tightly squeezed together on the same bench, elbows touching as they scrawl notes while the teacher talks and writes on a chalkboard. The metal sheet that serves as a roof makes the room hot and stuffy.